2021
DOI: 10.1371/journal.pone.0248052
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the medical malpractice cases against orthopedists in China between 2016 and 2017

Abstract: Background This study aimed to identify the most frequent reasons for orthopedic medical malpractice, gain insight into the related patient demographics and clinical characteristics, and identify the independent factors associated with it. Methods We collected and analyzed the demographic and injury characteristics, hospital levels and treatments, medical errors, and orthopedist’s degree of responsibility for the patients who were subject to orthopedic medical malpractice at our institution. Univariate and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The appraisers of the medical association are composed of more than three experts in the expert database, including clinical experts in relevant disciplines and one forensic expert. The identification procedures of the medical association can refer to the literature published by Hongzhi Lv et al [ 34 ]. As of October 1, 2018, the implementation of RPHMD further clarified the identification status of the medical association.…”
Section: Discussionmentioning
confidence: 99%
“…The appraisers of the medical association are composed of more than three experts in the expert database, including clinical experts in relevant disciplines and one forensic expert. The identification procedures of the medical association can refer to the literature published by Hongzhi Lv et al [ 34 ]. As of October 1, 2018, the implementation of RPHMD further clarified the identification status of the medical association.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, however, during the inspected time frame, the malpractice claims in Jiangsu and Zhejiang were more inclined to resolving through medical associations than other appraisal approaches, compared with other provinces in China. 18 …”
Section: Discussionmentioning
confidence: 99%
“…We summarized the previous literature reports [14,[25][26][27][28][29][30][31], after fully understanding those common factors and considering the reality of medical malpractice cases in China, and divided the influencing factors on the degree of causality into medical factors (91 technical faults and 29 non-technical faults) and 10 patient factors (S1 Table ). Regarding the attribution of medical malpractice, it is generally observed that an increased number of affirmative responses in medical factors correlates with a higher degree of hospital liability in the case.…”
Section: Plos Onementioning
confidence: 99%